Performance analysis of a PV/Diesel hybrid system for a remote area in Bangladesh: Effects of dispatch strategies, batteries, and generator selection. (15th February 2019) - Das, Barun K.; Zaman, Forhad
Abstract: This paper investigates the performance of PV/Diesel/Batt system for a stand-alone hybrid application in a remote community in Bangladesh meeting a load demand of 350 kWh/day with a 74.34 kW peak load demand. The effects of different dispatch strategies on the Cost of Energy (COE) and the Net Present Cost (NPC) using two major battery technologies (Lead Acid-LA and Lithium-ion) is studied. The study also extended to analyse the effects of selection of diesel generator in Hybrid Optimisation Model for Electric Renewables (HOMER) software tool on the performance indicators. Results indicate that the Combined Dispatch (CD) strategy has slightly lower Cost of Energy compared to the Load Following-LF and Cyclic Charging-CC strategies. However, operational emissions for Load Following Strategy is significantly lower than the other two strategies for both hybridised systems. The Renewable Fraction is greater in Load Following than the Combined Dispatch and Cyclic Charging strategies at the cost of Excess Energy (EE). The results also show that capital cost and the discount rate have a significant effect on Cost of Energy and Net Present Cost. However the fuel, battery, and PV module costs have negligible effects for both PV/Diesel/LA and the PV/Diesel/Li-ion-based hybrid systems. Highlights: Performance study of a stand-alone hybridised energy system is carried out. Effects of dispatch strategies, batteries, and generator selection are analysed. The Cost of Energy is comparable (∼0.32/kWh) between dispatch strategies. Load Following strategy has 40–50% lower CO2 emissions than CC and CD strategies.